Juridical Analysis Of The Crime Of Premeditated Murder Committed By Members Of The Police - Andri; Saiful Asmi Hasibuan (International Journal of Society and Law, 2024)
The function of the police, as regulated in Article 2, is to maintain public security and order, enforce the law, and provide protection and service to the community. Article 4 further states that the National Police of the Republic of Indonesia aims to achieve domestic security, uphold the law, and develop public peace while respecting human rights. The effective execution of these noble goals requires community support and cooperation. Importantly, police officers, as enforcers of the law, are not immune to it, as detailed in Article 29 Paragraph (1) of Law Number 2 of 2002 and Article 2 of Government Number 3 of 2003, which places police members under the jurisdiction of the general judiciary. Premeditated murder, defined as an intentional act to deprive another person of life with prior planning, carries severe legal consequences. This crime not only results in the loss of life but also has profound economic impacts on the victim’s family, potentially forcing children to drop out of school to support their family. Despite their duties, police officers can commit serious crimes, including premeditated murder, which are considered extraordinary due to their knowledge of the law. Claude Pomerleau defines such crimes as planned, systematic, and often targeting specific groups. A notable case is the premeditated murder by former Head of Division Ferdy Sambo at his official residence on July 8, 2022, which shocked the Indonesian public. Sambo was dismissed without respect after violating seven codes of ethics, highlighting the severe repercussions for police members involved in such crimes. This study examines the juridical aspects of premeditated murder committed by police officers, emphasizing the importance of legal accountability and ethical conduct within the force.